Leasing evaluation training as an alternative financing for MSME Seruni - Dwi Hartini Rahayu; Raflis Raflis; Husna Leila Yusran; Retno Sari Murtiningsih; Salim Budiman; Adinda Cintami Regalia; Abbraham Sahertian (Universitas Muhammadiyah Magelang, 2023)
Seruni is a business group formed since the Covid-19 Pandemic. The main problem of these MSMEs is the lack of capital they have so they have not been able to meet market demand. This training activity is a form of community service that aims to improve the financial literacy, especially regarding lease financing. The target of this program is to improve the skills of participants in making effective financial decisions so that this business will be able to develop and be sustainable in the future. The program began with conducting a pre-test, continued with the delivery of material and discussion, and closed with a post-test to find out the effectiveness of the program. Based on post-test result, it can be concluded that the understanding of the participants has increased after participating in this program.